Comment interpréter une revue ? Quelques pistes de lecture - Francis Mus (Contextes)
In this article, I study the “meaning” of a periodical, in two related ways: on the one hand I consider the “internal” interpretation of a periodical, on the other hand I look at its “external” impact. With regard to the (internal) interpretation of a periodical, two difficulties have to be taken into account. First, the discourse of the periodical deals with two different logics: one of the periodical itself and one of the individual authors. These logics constitute two different frameworks in which a text can be read. Second, one has to realize that the periodical does not function as a neutral mirror of reality, but that it has its proper dynamics. In determining the periodical’s impact, I work with the network-model, to which some “relief” has to be added in order to lay bare the impact of the different periodicals. Concretely, I will focus on the complex notion of believe, which functions as binder and holds the network together. All of this will be illustrated by way of the Belgian periodical L’art libre (1919-1922).